KEBEBASAN GAYA BERPACARAN DI LINGKUNGAN KOST - Lubis, Muhammad Alridho; Panjaitan, Nur Qomariah; Leva, Elia Arda; Ananta, Grestia; Mulyani, Nata Septi; Khotimah, Nurul; Andreani, Reva (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
The dating behavior of today's students has changed from the way it was in the past. Dating can be defined as the feeling of liking the opposite sex. But now a days it has been found that dating is like a husband and wife who can live in one house or a place where they can spend time together, such as in a boarding house. In the dating style of students in the city of Jambi, students no longer ignore the people around them; it even becomes a habit in the boarding environment around the city of Jambi. Many students start dating without knowing exactly what they are doing. This research is a type of qualitative research that uses descriptive analysis. This research is qualitative and uses descriptive analysis. The purpose of descriptive analysis is to provide an overview and understanding of the phenomena that occur in the field of student dating behavior. Observation, interviews, and documentation are the methods used to collect data in this study. Social control theory, labeling theory, and identity theory were used to analyze the results of the study, which showed that the behavior of free dating in the boarding house environment was increasingly troubling.